Design and implementation of an intelligent fuzzy VLSI chip for traffic control application - Islam, , Shabiu; Azim, , Anwarul; Bhuyan,, M. S; Jahan, , M. Saukat; Siddiquei, , H. R.; Othman, , Masuri (2006)
This paper describes a functional Fuzzy Traffic Controller (FTC), which utilizes fuzzy logic algorithm to achieve a smart and a flexible knowledge-based system in hardware design while achieving better efficiency in the traffic control and minimizing traffic jam occurrences at interchange on road area. To develop the system, the behavior level of FTC algorithm has developed using VHDL under MAX+PLUS II CAD environment. The designing part of FTC chip into VHDL program eliminates the shortcomings of other custom facilities and conventional controller design available today. The main goal is to overcome the bandwidth of existing systems. The Finite State Machine (FSM) of the FTC has coded in VHDL program for controlling the specific Traffic flow application. Later on, the FPGA Express (Synthesis tool) has used to get a fully gate level synthesis architecture for the whole Fuzzy based VLSI chip and then the optimization step has been applied for minimizing the VLSI chip's timing delay, clock speed, and area to get the correctness of FTC design. The main features of the FTC chip consist of various operational modes, safety features, capability, and robustness enhancement through fuzzy logic algorithm presented in this paper.